Parafrasa Lirik Lagu Bertema Pelacur Karya Iwan Fals - Hermintoyo, Muhamad (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
Song lyrics, just like poetry has a physical element and an inner element. In the hands of creative authors will look aesthetically pleasing by utilizing diction, rhymes, imagery and rhetorical means. The exact diction of the ability to capture the senses provides imagery, and setting on the lyrics he makes. Lyrics are generated from real life, squeally in the form of imagined imitations of life. The theme of nightlife is directly related to the perpetrators, such as prostitutes/ prostitutes/ prostitutes/ night butterflies/ tunasusila/ pramunikmat and other terms; bromocorah/ criminal/ residivis; striped nose guest and so on. Iwan Fals as a lyricist and songwriter was able to photograph the social life of the night world.  The lyrics of the song "Lonteku" paraphrasing the relationship of the prostitute who protects her boyfriend as a recidivist who is being pursued by officers.They have a special relationship. Their lives live each other accepting the circumstances and it is preserved. The lyrics to "Doa Pengobral Dosa" depict a low-end prostitute living in an unused train carriage, with cheap thick makeup, waiting for customers who don't come. His heart is worried about the fate of his children. Contradictory as a human being even though he worked contrary to religious morals, customs and state laws, he still mentioned his God in his prayer.